(untitled) (Philological Studies, 2019)
So far, in stylistics, there are attempts to produce punctuation marks, but their analysis is done along with the analysis of the words in the text. We think that we have a new challenge in the scientific research work within the stylistics. We are talking about bigger scientific work that we do within the stylistics.